PELATIHAN DAN PENGOLAHAN JAMUR TIRAM MENJADI ABON YANG BERGIZI DAN BERNILAI EKONOMIS TINGGI SEBAGAI UPAYA PENINGKATAN KONSUMSI DARI BUDIDAYA JAMUR DI DESA TENGGEREJO - Siti Shoimah; Eka Puspita Sari Maaidah; Wahyu Ginanjar A.S (Universitas YPPI Rembang, 2023)
Community service activities in Tenggerejo Village, Kedungping District, Lamongan Regency by processing oyster mushrooms into processed oyster mushroom shreds. Oyster mushroom cultivation has prospects for development because it has a high enough economic value so that it can increase household income. This study aims to provide skills and knowledge to the people of Tenggerejo to become entrepreneurs through the cultivation of oyster mushrooms, to describe the role of the oyster mushroom business which has high economic value in increasing household income, and to brand Tenggerejo village to become an oyster mushroom village. The approach method used is Focus Group Discussion which includes socialization, demonstration, training, coaching and evaluation. The materials used include processing the harvested oyster mushroom into shredded oyster mushroom so that the harvest can be processed into a durable product, demonstration of materials and tools used in processing shredded oyster mushroom, training on making shredded oyster mushroom and marketing training for shredded oyster mushroom through digital marketingKeywords: shredded mushrooms; white oyster mushroom; processing; marketing